Factors associated to the market value of professional soccer players - Sánchez, Mario; Orgaz, Begoña; Ramirez-Campillo, Rodrigo; Nakamura, Fabio Y.; Luis-Pereira, Jesús M.; Carretero, Manuel; Sánchez-Sánchez, Javier (Cuadernos de Psicología del Deporte, 2022)
The objective of this study was analysed to the market value (MV) of professional soccer players from Top-5 European Soccer Leagues. An ANOVA analysed the effect of the independent variables on the MV of the soccer players, with p<0.01. Soccer players from the Premier League (PL) showed greater MV compared to other leagues. Foreign soccer players showed greater MV compared to national soccer players. Soccer players between 21-30 years showed greater MV compared to those <21 and >30 years. Forward and midfielders showed greater MV compared to goalkeepers and backs. Soccer players that represented their countries at international matches showed greater MV compared to those that did not. The soccer players with a youth background formation in their clubs in the Premier League and La Liga showed greater MV compared to soccer players coming from other clubs. In conclusion, intrinsic and extrinsic factors affect the MV of soccer players. Research results may be useful to the sport managers in the selection of professional soccer players.